Quantitative Determination of Plasminogen - Bruhn, H. D; Müller, L; Duckert, F (Thrombosis and Haemostasis, 1970)
A modification of the caseinolytic assay for plasminogen is described. This assay system is characterized by the following features :1. Urokinase is used as activator achieving a complete activation of the plasminogen whereas with streptokinase caseinolytically inactive plasminogen-activator complexes are formed.2. All incubation times are reduced to the minimum which is still compatible with accuracy.3. Results are expressed in percent of a standard of ten normal plasmas.4. In this two-stage assay-system (activation of plasminogen to plasmin, digestion of casein by plasmin) both stages proceed simultaneously in the same system, thus the plasmin formed is stabilized “in statu nascendi” by the casein.5. Several conditions (stability of plasminogen in frozen plasma, use of anticoagulants, reproducibility) are defined.